Adoption and profitability of BARI released garlic varieties in Bangladesh: a farm level study (Asian-Australasian Journal of Food Safety and Security, 2023)
Garlic, a vital spice crop in Bangladesh, holds a prominent position as the leading producer among all spice crops. This study was conducted in three garlic growing districts, namely Rajbari, Natore, and Dinajpur, with the primary objective of assessing the adoption status of BARI garlic varieties, analyzing their farm-level profitability, and identifying constraints faced by the farmers. A total of 300 farmers, with 100 selected randomly from each district, participated in this research. Data collection was carried out using a pre-tested interview schedule during the period of January to March 2019. The findings revealed that BARI rosun-2 had the highest adoption rate among farmers, with 45% choosing this variety, while the adoption rate for BARI rosun-1 was the lowest at 14.67%. Interestingly, no adoption of the other two BARI varieties, BARI rosun-3 and BARI rosun-4, was observed in the study areas. Some farmers also cultivated local and exotic varieties, such as Italy, Patna, and Barma. The preference for BARI rosun-2 and BARI rosun-1 was attributed to their higher yield, greater profitability, and reduced susceptibility to insect-pest infestations at the farm level. Key cost items included human labor, seed cost, and the rental value of land. In terms of yield, the highest production was reported in Rajbari at 7,650 kg per hectare, followed by Natore (7,260 kg/ha.) and Dinajpur (6,980 kg/ha). Net returns were highest in Natore at BDT 69,631 and lowest in Dinajpur at BDT 38,613. The benefit-cost ratio (BCR) on the basis of variable cost and total cost were 1.31 and 1.24, respectively. The cost per kilogram based on total cost was BDT 32. The study identified low market prices during the peak season, the non-availability of improved or hybrid seeds, unfavorable weather conditions, and a lack of technical knowledge as major constraints to garlic cultivation. To address these issues, the study recommends measures such as banning excessive imports, introducing high-yielding hybrid varieties, providing hands-on training to interested farmers, and ensuring affordable input prices to promote higher adoption of these garlic varieties.In conclusion, this research sheds light on the adoption, profitability, and challenges of cultivating BARI garlic varieties in the specified districts, offering valuable insights for policymakers, farmers, and stakeholders in the garlic farming industry.Asian Australas. J. Food Saf. Secur. 2023, 7 (2), 73-90